THE ROLE OF MACHINE LEARNING IN SOCIETY (Modern education and development, 2025)
The article analyzes the role of machine learning technology in society and its impact on various sectors. Machine learning technology helps create innovations in society, increase efficiency, reduce errors, and improve decision-making. The article also highlights the positive impact of machine learning on the development of society and its future potential.